Sleep Duration and Age-Related Changes in Brain Structure and Cognitive Performance - Lo, June C; Loh, Kep Kee; Zheng, Hui; Sim, Sam K.Y.; Chee, Michael W.L. (Sleep (New York, N.Y.), 2014)
To investigate the contribution of sleep duration and quality to age-related changes in brain structure and cognitive performance in relatively healthy older adults. Community-based longitudinal brain and cognitive aging study using a convenience sample. Participants were studied in a research laboratory. Relatively healthy adults aged 55 y and older at study commencement. N/A. Participants underwent magnetic resonance imaging and neuropsychological assessment every 2 y. Subjective assessments of sleep duration and quality and blood samples were obtained. Each hour of reduced sleep duration at baseline augmented the annual expansion rate of the ventricles by 0.59% (P = 0.007) and the annual decline rate in global cognitive performance by 0.67% (P = 0.050) in the subsequent 2 y after controlling for the effects of age, sex, education, and body mass index. In contrast, global sleep quality at baseline did not modulate either brain or cognitive aging. High-sensitivity C-reactive protein, a marker of systemic inflammation, showed no correlation with baseline sleep duration, brain structure, or cognitive performance. In healthy older adults, short sleep duration is associated with greater age-related brain atrophy and cognitive decline. These associations are not associated with elevated inflammatory responses among short sleepers. Lo JC, Loh KK, Zheng H, Sim SK, Chee MW. Sleep duration and age-related changes in brain structure and cognitive performance.